Cellular senescence is a key mediator of lung aging and susceptibility to infection - Torrance, Blake L.; Haynes, Laura (Frontiers in Immunology, 2022)
Aging results in systemic changes that leave older adults at much higher risk for adverse outcomes following respiratory infections. Much work has been done over the years to characterize and describe the varied changes that occur with aging from the molecular/cellular up to the organismal level. In recent years, the systemic accumulation of senescent cells has emerged as a key mediator of many age-related declines and diseases of aging. Many of these age-related changes can impair the normal function of the respiratory system and its capability to respond appropriately to potential pathogens that are encountered daily. In this review, we aim to establish the effects of cellular senescence on the disruption of normal lung function with aging and describe how these effects compound to leave an aged respiratory system at great risk when exposed to a pathogen. We will also discuss the role cellular senescence may play in the inability of most vaccines to confer protection against respiratory infections when administered to older adults. We posit that cellular senescence may be the point of convergence of many age-related immunological declines. Enhanced investigation into this area could provide much needed insight to understand the aging immune system and how to effectively ameliorate responses to pathogens that continue to disproportionately harm this vulnerable population.